Evaluation the Collisional Stopping power and Continuous Slow Down Approximation ranges for protons in Carbon - Allah, Sabah Mahmoud Aman; Shaban, Shahad Abdul Salam (Sulaimani Journal for Pure and Applied Sciences, 2015)
The stopping power and CSDA ranges of energetic protons in carbon has been calculated using a model based on different theoretical approaches within energy range (1.5 -295)MeV . The present work accounts for the incident proton slows down due to the inelastic collision between target electrons of the medium and the incident proton moving through it . These interactions of the incident proton with the target’s electrons is a function of the proton energy . Our results are in good agreement available data of the universal code pstar . This calculation model can be useful for different applications in nuclear physics, medical physics , materials science and space radiation health.
Keywords: Stopping power of carbon; heavy charged Particle pstar; CSDA range; Mean ionization energy